Existência de soluções via métodos variacionais para uma classe de problemas quasilineares com expoentes variáveis - Ferreira, Marcelo Carvalho (2014)
In this thesis we establish existence and multiplicity results for solutions to some classes of problems on RN involving the p(x)-Laplacian operator. In the first part, we consider classes of problems dealing with nonlinearities possessing critical growth. Ultimately, we consider a class of problems with a nonlinearity possessing a subcritical growth. In this latter case, we searched for multi-bump solutions. Among the tools we used are Mountain Pass Theorem, Concentration-Compactness Principle, Lion s Lemma, Ekeland s Variational Principle and Penalization Method